VEGETATION ANALYSIS ESTIMATING BIOENERGY POTENTIAL AGROFORESTRY RUMBIA VILLAGE BOALEMO DISTRICT - Alexander Ruruh; Firman Syahputra; Sukma Ayu Haris; Zeinab Nurlena Y. Suma (Yayasan Adra Karima Hubbi, 2025)
Energy is one of the basic needs to support human survival. Along with the increasingly limited availability of energy from fossils, it is necessary to find other alternative energy sources. In the agroforestry area there are Aren plants which are one of the plants that can be processed into an energy source. the data used are primary and secondary data. Data analysis was carried out quantitatively and qualitatively. The results of the data analysis that have been carried out, found a total of 4 species at the tree level and 5 species at the pole level in Agroforestry in Rumbia. The highest important value at the tree level is Aren (Arenga pinnata) with a value of 155.95, the lowest Durian (Durio zibethinus) 21.53. the highest important value index at the pole level is Aren (Arenga pinnata) with a value of 144.42 and the lowest Chocolate (Theobroma cacao) 22.90.